Possible sources of long-term variations in the mid-latitude ionosphere - Elias, Ana Georgina (2011)
Trends in the upper atmosphere, together with the global warming of the lower atmosphere, are part of the global change of the Earth system. In the present work, which is focused in the upper atmosphere, long-term variations of the critical frequency of the ionospheric F2 layer, foF2, are studied in terms of the following possible causes: (1) longterm variations of the solar EUV radiation shown by the solar cycle length (SCL), (2) long-term variations in geomagnetic activity measured by the aa index, (3) the increasing greenhouse gases concentration in the lower atmosphere which would be producing a temperature decrease in the upper atmosphere, and (4) the Earth’s main magnetic field secular variation, which implies changes in the dip angle (I) affecting the thermospheric neutral winds that move the conducting plasma of the ionosphere. For this purpose, foF2 time series of four mid-latitude stations were processed. After filtering the solar activity effect, the long-term variability of these time series and that of the mentioned possible trend sources, were analyzed. The study of trends in the upper atmosphere is an important contribution to one of the present focus of climate science that is the determination of the extent to which human activities are altering the planetary energy balance through the emission of greenhouse gases and pollutants.